Effect of grazing on plant attributes and hydrological properties in the sloping lands of the East African highlands - Taddese, G.; Mohamed-Saleem, M.A.; Astatke, A.; Ayaleneh, W. (Springer, 2002)
Extending livestock grazing to the steep slopes has led to unstable grazing systems in the East African Highlands, and new solutions and approaches are needed to ameliorate the current situation. This work was aimed at studying the effect of livestock grazing on plant attributes and hydrological properties. The study was conducted from 1996 to 2000 at the International Livestock Research Institute at Debre Ziet Research Station. Two sites were selected: one at 0-4% slope, and the other at 4-8% slope. The treatments were: (1) no grazing (control); (2) light grazing, 0.6 animal unit months per hectare (aum/ha); (3) moderate grazing, 1.8 aum/ha; (4) heavy grazing, 3.0 aum/ha; (5) very heavy grazing, 4.2 aum/ha; (6) initially plowed and continuously very heavily grazed, 4.2 aum/ha. The result showed that species richness, infiltration rate, bare ground, and soil loss significantly varied with grazing pressure. Species richness was higher in grazed plots compared to nongrazed plots. Biomass yield improved on heavily grazed plots as cow dung accumulated over years. Cynodon dactylon plant species persisted with livestock grazing pressure in both sites. Infiltration rate improved and soil erosion declined in all treatments after the first year.